2012
DOI: 10.1038/ncomms1861
|View full text |Cite
|
Sign up to set email alerts
|

The Dishevelled-associating protein Daple controls the non-canonical Wnt/Rac pathway and cell motility

Abstract: Dishevelled is the common mediator of canonical and non-canonical Wnt signalling pathways, which are important for embryonic development, tissue maintenance and cancer progression. In the non-canonical Wnt signalling pathway, the Rho family of small GTPases acting downstream of Dishevelled has essential roles in cell migration. The mechanisms by which the non-canonical Wnt signalling pathway regulates Rac activation remain unknown. Here we show that Daple (Dishevelled-associating protein with a high frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 51 publications
7
77
0
Order By: Relevance
“…As a whole therefore, these genes may promote the development of follicles and oocytes but the mechanism is unclear. Previous studies have indicated that pathways involving the DEGs in this study also associate with reproduction except the Notch signaling pathway (Larkin et al, 1996;Lopez-Schier and St Johnston, 2001), TGF-beta signaling pathway (Shi and Massagué, 2003), steroid biosynthesis (Issop et al, 2013), MAPK signaling pathway (Xiao et al, 2007), Wnt signaling pathway (Habas and He, 2006;Ishida-Takagishi et al, 2012) and Jak-STAT signaling pathway (Kisseleva et al, 2002). However, the exact relationship between these signaling networks is not fully understood.…”
Section: Signaling Pathways In Reproductionmentioning
confidence: 68%
“…As a whole therefore, these genes may promote the development of follicles and oocytes but the mechanism is unclear. Previous studies have indicated that pathways involving the DEGs in this study also associate with reproduction except the Notch signaling pathway (Larkin et al, 1996;Lopez-Schier and St Johnston, 2001), TGF-beta signaling pathway (Shi and Massagué, 2003), steroid biosynthesis (Issop et al, 2013), MAPK signaling pathway (Xiao et al, 2007), Wnt signaling pathway (Habas and He, 2006;Ishida-Takagishi et al, 2012) and Jak-STAT signaling pathway (Kisseleva et al, 2002). However, the exact relationship between these signaling networks is not fully understood.…”
Section: Signaling Pathways In Reproductionmentioning
confidence: 68%
“…CCDC88C encodes DAPLE, a ubiquitously expressed protein that regulates cellular migration through its interaction with dishevelled in the non-canonical wnt pathway [46]. A mutation in CCDC88C was first suggested as the cause of hydrocephalus in a single consanguineous Algerian family [47], and was subsequently validated in a non-consanguineous Ashkenazi Jewish family and a consanguineous Palestinian family [48].…”
Section: Hydrocephalus Without Major Additional Physical Features (Tamentioning
confidence: 99%
“…Because Wnt5a stimulation correlates with Rac1 activity (9,23,24,27), we investigated whether the homeostatic Wnt5a arbitrated basal NF-kB activity in macrophages with concurrent CD14 expression is Rac1 dependent. Initially, we confirmed that Wnt5a-depleted macrophages harbor reduced levels of basally activated Rac1 by demonstrating an ∼50% reduced level of GTP-gS bound Rac1 in the Wnt5A siRNA-transfected RAW264.7 macrophages compared with the corresponding controls (Fig.…”
Section: Wnt5a-nf-kb-cd14 Axis In Macrophages Is Rac1 Dependentmentioning
confidence: 99%
“…The cytoplasmic adapter protein disheveled (Dvl), is crucial for both b-catenin2dependent and independent Wnt5a signaling (16-18, 23, 24). Contemporary research highlights how different cellular proteins orchestrate Dvl function (23,24). However, the precise biochemical mechanisms of Dvl coupling to the steady state versus activated conformations of ligand-receptor combinations of Wnt5a-Fz/ROR in different cell types are not completely understood.…”
mentioning
confidence: 99%